Numerical simulation of material flow in AA7075 during constrained friction processing - Diyoke, George; de Castro, Camila C.; Chafle, Rupesh; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Lightweight aluminum alloys, such as AA7075, are desirable for applications in various industries, but their limited formability and workability often pose significant challenges. Constrained Friction Processing (CFP) has emerged as a promising technique to address these challenges by refining microstructures through the relative motion between two tools and the workpiece. The process involves axial extrusion, dual tool rotation, and constraint of the extrudate to control material flow and enhance microstructural refinement. CFP is particularly attractive for high-strength AA7075 as it imposes constrained material flow and increased shear deformation, overcoming the limited formability observed in existing conventional extrusion processes. This study investigates CFP using both experimental and numerical methods, establishing correlations between process conditions, material flow, microstructural evolution, and hardness for the aluminum alloy AA7075. The process was investigated at rotational speeds of 1000–1400 rpm, resulting in the highest measured peak temperature up to 445°C and refined grain sizes of 2–3 µm. The results show that initial shear deformation and material flow under the rotating tools are redistributed during processing, leading to helical flow behavior in the extruded rod. The refined stir zone (SZ) exhibited increase in hardness, about 25% compared to the base material. The developed finite-element model demonstrates good agreement with experimental results with respect to the complete thermal cycle, spatial temperature distribution, and material flow patterns, providing insight into the microstructural evolution during CFP of aluminium alloys.
Keywords: Process Simulation; Constrained Friction Processing (CFP); Material Flow Behavior; Dynamic Recrystallization; Microstructural Zones